1991
DOI: 10.1159/000182185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Hormone on Glucose Metabolism

Abstract: Growth hormone (GH) counteracts in general the effects of insulin on glucose and lipid metabolism, but shares protein anabolic properties with insulin. Under physiological circumstances GH does not affect total glucose turnover directly. There is however evidence that GH acutely decreases glucose oxidation (secondary to an increase in lipid oxidation) and suppresses muscle uptake of glucose, suggesting that GH redistributes glucose fluxes into a non-oxidative pathway, which could be a build up of glycogen depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Subjects received carbohydrates equivalent to 1.5 g. kg -1 of body weight and it seems that this amount of carbohydrates is not enough to alter the response of the pituitary and hypothalamus in the release of β-endorphin. Only one other study examined the response of β-endorphin to carbohydrate and fat meals and found similar results with this study since β-endorphin response changed in the obese but not in individuals of normal weight [5]. β-Endorphin did not increase significantly until at the exhaustion time point.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Subjects received carbohydrates equivalent to 1.5 g. kg -1 of body weight and it seems that this amount of carbohydrates is not enough to alter the response of the pituitary and hypothalamus in the release of β-endorphin. Only one other study examined the response of β-endorphin to carbohydrate and fat meals and found similar results with this study since β-endorphin response changed in the obese but not in individuals of normal weight [5]. β-Endorphin did not increase significantly until at the exhaustion time point.…”
Section: Discussionsupporting
confidence: 83%
“…β-endorphin is one of the peptides that has been suggested to play a role in glucose metabolism at rest [4,5] and during exercise [6-9]. β-endorphin is an opioid peptide representing the C-terminal 31 amino acid residue fragment of pro-opiomelanocortin.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports have identified the metabolic response to GH in normal and GH-deficient patients in the regulation of protein, glucose and lipid metabolism [62,63]. …”
Section: Metabolomic Markers In Patients With Ghdmentioning
confidence: 99%
“…These hormonal changes lead to remarkable alterations in lipid and glucose metabolism. GH, in particular, has a significant lipolytic effect and potentiates elevated glucose levels, which appears to counteract the effects of insulin [ 9 ]. Supplementation of GH for long periods, especially longer than 21 days, significantly reduced fat accumulation in rats [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%